2017
DOI: 10.1177/1010428317698389
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a acts as a tumor suppressor in colorectal cancer by targeting eIF4A1

Abstract: Emerging evidence indicates that microRNAs play critical roles in carcinogenesis and cancer progression. In this study, miR-133a was found to be significantly downregulated in colon tumor tissues. We aimed to determine its biological function, molecular mechanisms, and direct target genes in colorectal cancer. From these results, we found that miR-133a was significantly downregulated in primary tumor tissues and colon cancer cell lines. Ectopic expression of miR-133a in colon cancer cell lines significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Additionally, we found that EIF4A1 was a target of miR-599. Li et al unraveled that miR-133a could decelerate the progression of colorectal cancer by targeting EIF4A1 [30]. Wei et al demonstrated that EIF4A1 could function as a target of miR-1284 to participate in the regulation of GC [20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that EIF4A1 was a target of miR-599. Li et al unraveled that miR-133a could decelerate the progression of colorectal cancer by targeting EIF4A1 [30]. Wei et al demonstrated that EIF4A1 could function as a target of miR-1284 to participate in the regulation of GC [20].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-133a has been reported as a tumor suppressor in several cancer types, such as glioma, colorectal cancer, etc. ( 31 , 32 ). For OS, miR-133a down-regulation is associated to unfavorable prognosis in patients with OS ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs typically bind to the mRNA 3′-UTR of its target gene or directly cut the mRNA at a post-transcriptional level, thereby inhibiting the expression of the target gene ( 5 , 6 ). miR-133a has been reported to be an antioncogene, which was correlated with cell development, proliferation and prognosis in colon cancer, oral squamous cell carcinoma and gastric cancer ( 14 , 16 , 27 ). In the present study, we verified that USP39 was a direct target of miR-133a in gastric cancer cell lines GC-27 and MGC-803.…”
Section: Discussionmentioning
confidence: 99%
“…In oral squamous cell carcinoma, miR-133a inhibits cell proliferation and invasion by suppressing COL1A1 ( 14 ). Furthermore, in colorectal cancer, miR-133a acts as a tumor suppressor to inhibit cell growth and migration by targeting elF4A1 in vitro ( 15 ). In addition, miR-133a had a low expression and inhibited cell proliferation, invasion and induced apoptosis in gastric carcinoma cells ( 12 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%